Comparison of the effect of Zingiber officinale extract and antibiotics on Staphylococcus aureus isolated from door handles in the Department of Biology - Marwa M. Mahdi (Tikrit Journal of Pure Science)
This study was conducted at the College of Science - Department of Life Sciences where it examined the effect of Zingiber officinale alcoholic extract and some antibiotics (Levofloxacin, Vancomycin, Nitrofurantion, Oxacillin) on isolates of Staphylococcus aureus, which were isolated from door handles in the College of Sciences, University of Tikrit, Department of Biology, and through the obtained results the S. aureus was sensitive to all three concentrations (25 – 50 – 75)% of the alcoholic extract, but it was differentially sensitive to the antibiotics as the strongest effect and the largest area of ​​inhibition was for Levofloxacin 5 µg (LEV-5), the diameter of the inhibition zone was (22 mm) compared to the other antibiotics that showed clear and convergent inhibition zones, but less in diameter than LEV-5.